2017
DOI: 10.3389/fpsyg.2017.02119
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Prosocial Tendencies in Germany: Sources of Validity and Reliablity of the Revised Prosocial Tendency Measure

Abstract: The prosocial tendencies measure (PTM; Carlo and Randall, 2002) is a widely used measurement for prosocial tendencies in English speaking participants. This instrument distinguishes between six different types of prosocial tendencies that partly share some common basis, but also can be opposed to each other. To examine these constructs in Germany, a study with 1067 participants was conducted. The study investigated the structure of this German version of the PTM-R via exploratory factor analysis, confirmatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 63 publications
1
37
0
2
Order By: Relevance
“…In line with previous findings (e.g. Rodrigues et al, 2017), our results showed that different basic personality traits were related to different prosocial tendencies. However, Agreeableness was the trait most consistently related to prosocial tendencies (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous findings (e.g. Rodrigues et al, 2017), our results showed that different basic personality traits were related to different prosocial tendencies. However, Agreeableness was the trait most consistently related to prosocial tendencies (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Since some of the subscales in their pilot studies loaded on two distinct factors, Carlo and Randall (2002) also added anonymous (defined as helping performed without others being aware of who had helped them) and dire (helping in crisis or emergency situations) prosocial behaviour, which were derived from public prosocial behaviour and emotional prosocial behaviour, respectively. Due to the differences between these types of behaviour and the underlying motivation, it is not surprising that different types of prosocial behaviour are related to different personality traits (Rodrigues, Ulrich, Mussel, Carlo, & Hewig, 2017). Within the Big Five space, traits that may be linked to prosocial behaviour are Extraversion (as extraverts might be more willing to perform thoughtless acts that may be linked to heroic prosocial behaviour) and Neuroticism (since high anxiety and vigilance to threat can undermine helping).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, we assess the influence of demographic, environmental and altruistic factors on WTP for these labels. We use the New Environmental Paradigm (NEP) [14], Attitude towards Helping Others (AHO) [15] and Altruistic Social Behaviour (ASB) [16][17][18] scales as they are among the most widely reviewed and accepted environmental and altruistic scales. Lastly, we provide a description of consumers' association of WTP for the labels by estimating their revealed correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Altruistic behavior has been defined as a voluntary action intended to benefit another person without the expectation of receiving external rewards or avoiding externally produced aversive stimuli or punishments ( Eisenberg and Miller, 1987 ). However, this broad motive definition of altruism has been further narrowed down in a factor-analytical conceptualization ( Carlo et al., 2003 ; Carlo and Randall, 2002 ) where prosocial behavior has been categorized according to their driving motives into six different categories (see also Rodrigues et al., 2017 for validation in German). Among these six categories was altruism, defined by Carlo and Randall (2002) , seeing altruism or altruistic prosocial behavior as “voluntary helping motivated primarily by concern for the needs and welfare of another, often induced by sympathy responding and internalized norms/principles consistent with helping others” ( Carlo et al., 2010 , p. 273).…”
Section: Introductionmentioning
confidence: 99%